Implikasi Aksiologi Ilmu Terhadap Implementasi Qanun Aceh: Pemahaman Nilai dan Etika: Implications of Axiological Science for the Implementation of Aceh's Qanun: Understanding Values ​​and Ethics - Ulya, Nur Afina; Robbaniyah, Nur; Astuti, Widia (Jurnal Filsafat Indonesia, 2024)
This study discusses the implications of the axiology of science on implementing the Aceh Qanun, a collection of legal regulations in force in Aceh. Axiology, which is a field of study that emphasizes the use of values and ethics in science, tries to find loopholes in the impact of applying values and ethics in the context of the Aceh Qanun. This research shows that the application of the axiology of science has an existence in the implementation of the Aceh Qanun such as strengthening Aceh's local cultural identity and preserving Islamic teachings which have been a feature of law in Aceh for a long time. The public often does not understand the implementation of the Aceh Qanun because of the dualism of the rules in Aceh. Therefore in this paper, the author will explain how the axiology of science can be the basis for understanding the legal system. This study concludes that the application of scientific axiology to the implementation of the Aceh Qanunhas a positive impact in ensuring an understanding of values and ethics in the policies implemented. It is important in the future to consider aspects of justice, equity, social welfare, and harmonization of national law in maintaining the stability of the statutory hierarchy. Another implication is seen in the contribution of science axiology as a strong foundation for policies that reflect the needs of society. This study uses a qualitative method with library research on various books and journals that can be used as a reference for the development of the Aceh Qanun and its implementation.